The Life of Judaism - Goldberg, Harvey E. (Book collections on Project MUSE., 2001)
Approximately thirteen million people around the world define themselves as Jews, with the majority residing in the United States and Israel. This collection portrays the diversity of Jewish experience as it is practiced and lived in contemporary societies.